2021
DOI: 10.20944/preprints202010.0172.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of Indoleamine 2,3-Dioxygenase Influenced the Age Onset of Parkinson’s Disease

Abstract: Aims Earlier studies reported alterations of the kynurenine (KYN) pathway of tryptophan (TRP) metabolism in Parkinson’s disease (PD). The first rate-limiting enzymes indoleamine 2,3- dioxygenase (IDO) and tryptophan dioxygenase were observed upregulated, resulting elevated KYN/TRP ratios in the serum and cerebrospinal fluid samples of patients with PD. An increasing number of single nucleotide polymorphisms (SNPs) has been identified in a population of PD. However, little is known if genetic variatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Increased 3-HK levels in CSF and a lower KYNA/KYN ratio, increased QUIN levels, and higher QUIN/KYNA ratio were reported in plasma of PD patients [186,187]. In addition, it is reported that the single nuclear polymorphism variants of IDO1 influence the age onset of PD [188]. PD had strong effect sizes for shared deficits in complex I and IV in the peripheral blood, frontal cortex, cerebellum, and substantia nigra [173].…”
Section: Parkinson's Diseasementioning
confidence: 98%
“…Increased 3-HK levels in CSF and a lower KYNA/KYN ratio, increased QUIN levels, and higher QUIN/KYNA ratio were reported in plasma of PD patients [186,187]. In addition, it is reported that the single nuclear polymorphism variants of IDO1 influence the age onset of PD [188]. PD had strong effect sizes for shared deficits in complex I and IV in the peripheral blood, frontal cortex, cerebellum, and substantia nigra [173].…”
Section: Parkinson's Diseasementioning
confidence: 98%
“…Increased 3-HK levels in CSF and a lower KYNA/KYN ratio, increased QUIN levels, and higher QUIN/KYNA ratio were reported in plasma of PD patients [ 205 , 206 ]. In addition, it is reported that the single nuclear polymorphism variants of IDO1 influence the age onset of PD [ 207 ]. PD had strong effect sizes for shared deficits in complex I and IV in the peripheral blood, frontal cortex, cerebellum, and substantia nigra [ 192 ] ( Table 2 ).…”
Section: Diseases Linked To Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Van Gool et al also found a connection between IFN-α immunotherapy and psychiatric side effect [90]. IFN-α induces IDO, which converts TRP to KYN leading to a shortage of 5-HT, which may result in depression [38,91] (Table 1). IDO induction, a switch toward the TRP-KYN metabolic pathway and the disruption of the equilibrium between neurotoxic and neuroprotective actions all confirm the significance of KYN system activation in depression [92].…”
Section: Kynurenine Aminotransferasesmentioning
confidence: 99%